Renal aging and its consequences: navigating the challenges of an aging population - Meiqi Zhang; Haifeng Ni; Yumeng Lin; Ke Wang; Tingke He; Lan Yuan; Zhongyu Han; Xiaohong Zuo; Xiaohong Zuo; Xiaohong Zuo (Frontiers in Pharmacology)
With the aggravation of population aging, kidney aging and its impact on health have been widely concerned. Renal aging not only involves structural and functional changes but also is significantly linked to the occurrence and progression of some kidney diseases. Mechanisms of renal aging include oxidative stress, reduced Klotho levels, cellular senescence, and chronic inflammation. These changes lead to a sustained reduction in renal filtration, reabsorption, secretion, as well as endocrine function, which in turn affects overall health. Renal structural changes mainly include glomerulosclerosis, tubular degeneration and interstitial fibrosis. These structural changes are closely related to the decline of kidney function and may lead to the occurrence of chronic kidney disease (CKD). In addition, elderly individuals experience a higher rate of acute kidney injury (AKI) and face poorer prospects for recovery. The prevalence of age-related kidney disease, especially diabetic nephropathy (DN), increases with age. End-stage renal disease (ESRD) refers to the most advanced stage of CKD, in which the kidneys of patients show signs of premature aging compared with those of healthy people. Measures to prevent and delay renal aging in daily life, including healthy lifestyle, proper diet, and adequate exercise, are also discussed in this manuscript.